PENGARUH GOLD PRICE DAN LOAN INTEREST RATES TERHADAP ACCOUNTS RECEIVABLE PADA PT PEGADAIAN (PERSERO) - Ramli, Anwar; Nurman, Nurman; Karmila, Yusri (Universitas Dharmawangsa, 2024)
PT Pegadaian (Persero) is one of the BUMN that has an important role in providing financing services with collateral, one of which is gold. One of the factors that can affect the financial performance of PT Pegadaian is the gold price and loan interest rates. Both play an important role in determining the volume and quality of the company's receivables, especially those related to pawn financing. So the purpose of the article is to determine the effect of gold price and loan interest rates on accounts receivable at PT Pegadaian (Persero) in Makassar City. This study was conducted at PT Pegadaian in Makassar City. The data collection method used interviews, documentation studies, observations. The data analysis technique used in this study is statistical analysis. Therefore, the data must be quantitative data. The results and discussion, it can be concluded that: 1) The impact of gold price has a significant positive effect on accounts receivable at PT. Pegadaian. The impact of gold price plays an important role in the pawn business, especially at PT Pegadaian, which is the main collateral for loans. Fluctuations in gold prices have a direct impact on the value of collateral, which in turn affects the amount of loans that can be disbursed by PT Pegadaian. When the gold price increases, the value of collateral increases, allowing PT Pegadaian to offer higher loans. This of course causes an increase in the volume of pawn transactions and accounts receivable; 2) The impact of loan interest has a significant negative effect on accounts receivable at PT. Pegadaian. The impact of loan interest plays an important role in shaping borrowers' decisions. When loan interest is low, the cost of borrowing is more affordable, and this encourages more people to take out loans. As a result, this leads to an increase in the number of pawn transactions, which in turn results in an increase in accounts receivable at PT Pegadaian. To manage receivables effectively, PT Pegadaian needs to monitor changes in gold prices and loan interest closely, adjusting its lending policies as necessary to optimize the balance between loan volume and receivable quality. By understanding and anticipating the impact of these factors, PT Pegadaian can better manage risk.